On the synergetic interactions between termite soldiers and workers - Castiblanco Quiroga, Gladys Julieth (Universidade Federal de Viçosa, 2016)
A common response to predation pressure in social animals has been to allocate some individuals to defence tasks. In termites, the evolution of soldier caste was the most extreme anti-predatory response, because they are highly specialized in defence, sterile and incapable of perform self-maintenance. However, many studies have shown the active role of soldiers in tasks of space exploration like foraging. Such observations are important because the high contribution of workers in defence suggest some redundancy rate of soldier caste in termite colonies. The redundancy seems occurs in Cornitermes cumulans, where the workers being more responsive to threats than soldiers. Here we hypothesized that one way to diminish the cost of soldiers is that they are capable to do more than only defence. Specifically, we anticipate that soldiers are capable to optimize the search strategy of the workers. In the walking experiment with C. cumulans we find that the mean speed of the workers increases nonlinear with the number of soldiers. This result and the pre- sence of patterns highly coherent with Lévy flight motion suggests that the soldiers strengthen the exploratory capacity of workers in C. cumulans. In doing so, soldiers are expected to provide significant contributions to the intake of resources and to decreasing mortality in the colony. Then, our results propose an intrinsic advantage of have soldiers in the colony, and this may diminish the cost of soldiers in termite colonies.

Uma resposta comum de animais sociais à pressão de predação é alocar alguns indivíduos para a função de defesa. Em cupins, a evolução da casta de soldados, parece ter ocorrido como uma resposta extrema a predação, uma vez que são morfofisiologicamente adaptados à defesa, estéreis e incapazes de se alimentarem sozinhos. No entanto, Vários estudos têm mostrado a participação ativa da casta de soldados em tarefas de exploração do espaço como forrageio. Ditas observações são relevantes pois a alta contribuição dos operários em defesa sugere que os soldados tem um grau de redundância nas colônias de cupins. Tal redundância parece ocorrer em Cornitermes cumulans, no qual os operários são mais participativos que os soldados na defesa do ninho. Aqui nós hipotetizamos que uma forma de diminuir o custo da casta de soldados é que eles sejam capazes de fazer mais do que só defender. Especificamente, prevemos que tal contribuição deve ser otimizar estratégias de busca. No experimento de caminhamento com C. cumulans encontramos que a velocidade média de deslocamento dos operários cresce não-linearmente com a presença de sol- dados. Esse resultado e a presença de padrões de movimento altamente coerentes com vôo de Lévy sugerem que os soldados reforçam a capacidade exploratória dos operários em C. cumulans. A eficiência na exploração do espaço na presença de soldados pode estar contribuindo na entrada de recursos na colônia e na diminuição da mortalidade. Assim, nossos resultados mostram uma vantagem intrínseca de ter soldados na colônia, o que pode diminuir o custo dos soldados nas colônias de cupins.
Keywords: Térmita - Comportamento; Térmita - Defesa; Cornitermes cumulans; Ciências Agrárias; Agronomia; Fitossanidade; Entomologia Agrícola